Microsampling and conventional sampling techniques for quantification of tacrolimus in blood samples: A systematic review - Muthia Hanifah; Yahdiana Harahap; Denni Joko Purwanto (Eduvest - Journal of Universal Studies, 2024)
Tacrolimus is immunosuppressive drugs that have a narrow therapeutic range, and a large inter-patient variability in their pharmacokinetics. Serial monitoring of tacrolimus after transplantation is important to ensure the concentration in biological fluids is maintained at the therapeutic range. Blood sampling for therapeutic drug monitoring of tacrolimus is mostly by venipuncture, making it inconvenient and invasive due to repeated sampling. Thus, microsampling has been adopted as an alternative for sample collection as it is less invasive and more convenient for patients. This article aims to review validated bioanalysis methods for tacrolimus to compare the methods using venous sample and microsampling methods. Related studies about tacrolimus analysis method in blood samples were screened from several databases and summarized with PRISMA flow diagram. A total of 12 studies were considered eligible and reviewed in this article. This systematic review provides a narrative of sample quantification of tacrolimus that collected by venipuncture and microsampling method, its bioanalytical method employed to perform the analysis, and clinical validation or application to patients with organ transplants. Studies with microsampling methods have been validated and applied to the patients. Some studies that compared both methods concluded there is no significant difference between tacrolimus concentrations by venipuncture or microsampling methods. Therefore, microsampling can be considered an option for future development of sampling method in tacrolimus routine monitoring.